CATHOLICISM AND ITS BELIEFS: THE CHARM OF CATHOLIC SPIRITUALITY IN INTEGRAL HEALTH CARE - Chagas Ramos, Rawy (Revista Gênero e Interdisciplinaridade, 2025)
This article explores the relationship between Catholicism and holistic healthcare, emphasizing how Catholic spirituality shapes practices of care, rituals, and ethical decisions in contexts of illness, suffering, and death. Through an interdisciplinary approach involving Theology, Religious Studies, and Health Sciences, the work highlights the significance of sacraments, pastoral health ministry, and palliative care in promoting a more humanized health assistance. It advocates for the integration of spiritual care as an essential component of compassionate, ethical, and person-centered care, fostering a culture grounded in dignity and Christian hope.